Private well water stewardship in rural Georgia. - J Edward Dotherow; Bettye Apenteng; Andrew Hansen; Asli Aslan (PLoS ONE)
This study sought to identify the psychosocial influences on the practice of well stewardship behaviors (water testing, water treatment, and well maintenance) in rural Georgia, USA. Three interventions (education, the provision of household water treatment systems [HWTS], and both education and HWTS) were evaluated using a four-group, randomized controlled trial. A total of 64 private well owners completed a pretest measuring psychosocial factors and stewardship behaviors before receiving an intervention. Following a 104-day waiting period, participants completed a posttest and interviews were conducted to identify the barriers and facilitators to use (S1 File). Pretest results showed that 34% of well owners have ever tested their water and that only 25% treat their water before consumption. The education-only intervention showed no influence on stewardship behaviors, resulted in no new water tests and had no impact on psychosocial factors. The HWTS-only intervention had no significant effect on testing and treatment behaviors, though it had a significant effect on abilities (R2 = .87, p< 0.05) and self-regulation (R2 = 1.0, p<0.01). The intervention of both education and HWTS had no effect on testing and no significant effect on treatment behaviors, though had a significant effect on abilities (R2 = .84, p<0.05) and self-regulation (R2 = .93, p<0.05). This study identified three barriers to the use of HWTS: beliefs, knowledge, and functionality. Two factors (piece of mind and ease of use) were identified as facilitators to the use of HWTS. The results of this study indicate that providing water treatment systems does not guarantee use and that current educational efforts provided by state and local health departments may be ineffective.